You have new items in your feed. Click to view.
Q: solve for x. a(bx-2)=cx+12
A: a(bx - 2) = cx + 12 abx - 2a = cx + 12 abx - cx = 12 + 2a (ab - c)x = 12 + 2a x = (12 + 2a)/(ab - c)
Original conversation
User: solve for x. a(bx-2)=cx+12

Question
Updated 8/20/2014 12:11:23 AM
This conversation has been flagged as incorrect.
Flagged by yeswey [8/20/2014 12:10:18 AM]
Rating
3
a(bx - 2) = cx + 12
abx - 2a = cx + 12
abx - cx = 12 + 2a
(ab - c)x = 12 + 2a
x = (12 + 2a)/(ab - c)
Confirmed by jeifunk [8/20/2014 12:12:24 AM]

Questions asked by the same visitor
y+7=5-9y
Weegy: y = 8 (More)
Question
Updated 8/20/2014 12:12:55 AM
y + 7 = 5 - 9y
y + 9y = 5 - 7
10y = -2
y = -2/10 = -1/5

Confirmed by jeifunk [8/20/2014 12:15:36 AM]
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 247 [Total 265] Ratings 0 Comments 177 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 125 [Total 276] Ratings 1 Comments 5 Invitations 11 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.